The Bourne supremacy : a novel - Ludlum, Robert, 1927-2001 (Bantam Books, 2012)
Super-diplomat Raymond Havilland sets up the kidnapping of Jason Bourne's wife, in order to draw Bourne out of retirement and into a Taiwanese plot to seize Hong Kong and incite China against the West.